Neoadjuvant pertuzumab plus trastuzumab in combination with anthracycline- free chemotherapy regimen in patients with HER2 positive breast cancer–Real-world data from a single center in India. (2021) - Arora, Shalabh; Gogia, Dr. Ajay; Deo, SVS; Sharma, Dayanand; Mathur, Sandeep R
Highlights: There is paucity of data regarding NACT incorporating dual HER2 blockade in Indian patients, both in trials as well as real world setting. This study confirmed the safety and efficacy of TCHP (docetaxel, carboplatin, trastuzumab, & pertuzumab) chemotherapy regimen for patients with early, locally advanced or oligometastatic HER2 positive breast cancer. TCHP results in high pathological complete response rate with an acceptable toxicity profile even in oligometastastic disease. This study supports incorporation of pertuzumab in NACT to prevent more expensive TDM1 in adjuvant setting (for patients not achieving pathological CR). Abstract: Background: Dual targeted therapy with chemotherapy is one of the therapeutic approaches as neoadjuvant treatment in HER2/neu positive breast cancer (BC). However, the safety and efficacy data of dual-targeted, chemotherapy regimen (docetaxel, carboplatin, trastuzumab, & pertuzumab [TCH-P] is limited from the Indian subcontinent. Methods: This retrospective study aims to evaluate the efficacy and toxicity of neoadjuvant TCH-P regimen in early, locally advanced, and oligometastatic (OM) HER2-positive BC, at All India Institute of Medical Sciences, New Delhi, India, in between the period 2015–2020. Total 6 cycles of 3-weekly neoadjuvant chemotherapy (NACT) protocol containing docetaxel (75 mg/m2), carboplatin (AUC = 6), trastuzumab (8 mg/kg loading followed by 6 mg/kg) and pertuzumab (840 mg loading followed by 420 mg) were planned. Subcutaneous peg-filgrastim was prophylactically administered on day 2 of each cycle. The primary outcome was the pathological complete response (pCR), and secondary outcomes were clinical overall response rate (ORR), rate of breast conservation surgery (BCS) for patients for whom modified radical mastectomy (MRM) was planned and toxicity. Results: Forty-five patients with a median age of 48 years (31–65) were included in this study. The TNM (AJCC-7th edition) stage distribution was stage II, 14 (31.1%); stage III, 29 (64.5%); and stage IV (OM), 2 (4.4%). Clinical node positivity disease was found in 26 (57.8%) cases. Nineteen (42.2%) patients had hormone-positive and 26 (57.8%) cases were premenopausal. The clinical ORR and CR were seen in 100% and 60% respectively. Overall pCR rate was observed in 25 (55.6%) patients (70% in stage II). BCS was performed in 23 (51.1%) cases. In 12 (26.6%) cases, planned MRM was changed to BCS following NACT. Grade 3 and 4 toxicities were diarrhea 7 cases, thrombocytopenia in 6, neutropenia in 4, febrile neutropenia in 1, and anaemia in 2 cases. Ten patients required dose modification. No patient had congestive heart failure or induction death. Conclusions: This is the first study of the non-anthracycline-based neoadjuvant protocol in HER2 positive BC from India. The TCH-P is an effective, safe, and well tolerated protocol with a pCR rate of 55.6% and 26.6% BCS conversion rate from planned MRM.